COUPLING BEAM DESIGN WITH SPECIAL MOMENT FRAME AND SPECIAL REINFORCED CONCRETE SHEAR WALLS - Agyanata Tua Munthe; Muklish Nalahuddin (NAROTAMA UNIVERSITY, Indonesia, 2019)
An Earthquake is on of the natural phenomena that cannot be avoided or cannot be prevented by its appearance which is very difficult to accurately predict both from the time and place of its occurrence. Shear wall system is used to increase the sitffness of many multi-storey building, in this case building that have more than 20 floors. Building structures with shear wall as retaining element of lateral force generally have good performance during an earthquake. Coupling beam is an connecting beam betweem two shear walls, this beam makes a series of shear walls works as a system that is able to withstand earthquake force. Coupling beam also make the working structure rigid and absorbs energy due to the very high rigidity of the coupling beam with shear wall behaving link two free cantilevers. Coupling beam is considered to be able to transmit shear force from one wall to another so that it can withstand large structural deformation. Structure design material strenght for concrete fc’ 35MPa fc 55’MPA and rebar (D10 & D13) using fy 520MPa and fy 420MPa for diameter >16mm. While the regulations used are SNI 1726: 2012, SNI 1727: 2013, and SNI 2847: 2013. Structural loading is given according to loading rules which are then analyzed using ETABS 2016 software.